Efficacy and long-term tuning parameters of vagus nerve stimulation in long-term treated depressive patients - Mueller, Helge H. O.; Luecke, Caroline; Moeller, Sebastian; Philipsen, Alexandra; Sperling, Wolfgang (Journal of Clinical Neuroscience, 2017)
Vagus nerve stimulation (VNS) is a promising neurostimulation tool for the treatment of treatment-resistant depression. Here, we report the effects of positive remission rates and tuning parameters in a group of 18 (6 female, 12 male, mean age 54) long-term treated patients. Treatment varied between 3 and 200months (mean 104.9months). Mean stimulation intensity was 1.46mA, ranging from 0.5 to 2.0mA and high-frequency stimulation of 20-25Hz (mean 23.61Hz). The remission rates in our study population clearly indicate ongoing positive effects of VNS and highlight stimulation tunings between 0.5 and 2.0mA and 20-25Hz as best dosage for achieving remittance in long-term treatment of VNS.
EVALuna2:33574